Znaczenie świadomości pracowników w normatywnych systemach zarządzania - Goranczewski, Bolesław; Puciato, Daniel (Meaning of Employees' Awareness in Standard Managing Systems, 2008)
The article discusses the essence of awareness of employees performing according to standard managing systems. Such factors like: references, training, leadership, motivation ,company culture were described in the first part. The next part is on employees' awareness in connection with ISO series 9000, 14000, and PN 18000. Norms were chosen according to their spread, generality, and independence. The last part presents a fragment of survey connected with efficiency and effectiveness of managing quality systems in heating plants. The evidence brings closer a range of problems related to the level of awareness of system users (proxies, internal auditors, process owners, documents authors) The article ends with short resume. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 413-424